2022
DOI: 10.24883/iberoamericanic.v12i.2022.e0411
|View full text |Cite
|
Sign up to set email alerts
|

Post-Pandemic Reflections on Challenges and Opportunities for Marketing Research in the 21st Century

Abstract: The role of marketing is evolving rapidly, and design and analysis methods used by marketing researchers are also changing. These changes are emerging from transformations in management skills, technological innovations, continuously evolving customer behavior, and most recently the Covid-19 pandemic. But perhaps the most substantial driver of these changes is the emergence of big data and the analytical methods used to examine and understand the data. To continue being relevant, marketing research must remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…As the repository was generated by specialized agencies and made available in a ready-touse fashion to researchers, possible issues related to common method bias, non-response bias and multicollinearity did not affect this study. Likewise, the questions in our measurement model were single-item constructs, so internal consistency and convergent/discriminant validity of the measurement model were ensured by definition (Hair et al, 2022;Sarstedt et al, 2021).…”
Section: Questionnaire Design Data Collection and Sample Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the repository was generated by specialized agencies and made available in a ready-touse fashion to researchers, possible issues related to common method bias, non-response bias and multicollinearity did not affect this study. Likewise, the questions in our measurement model were single-item constructs, so internal consistency and convergent/discriminant validity of the measurement model were ensured by definition (Hair et al, 2022;Sarstedt et al, 2021).…”
Section: Questionnaire Design Data Collection and Sample Descriptionsmentioning
confidence: 99%
“…We conducted both collinearity checks and path coefficient p-value tests (Hair et al, 2022;Sarstedt et al, 2021) as well as we assessed the Q 2 values to evaluate the predictive power of endogenous constructs. We found that this model has no predictive relevance, as Q 2 < 0 (Hair et al, 2019a, b).…”
Section: Pls-sem and Hypotheses Testingmentioning
confidence: 99%
“…According to Oh et al (2022), the product innovation performance of companies varies between countries since certain consumer characteristics (consumer sophistication, creativity, global identity, and local identity) influence the product innovation performance of companies, which can affect the creation and the success of innovative products. In this scenario, Hair, Harrison, and Risher (2022) point out that marketing is also evolving rapidly, and these changes are emerging from transformations in management skills, technological innovations, and the evolution of consumer behavior.…”
Section: Product Innovation and Sustainable Developmentmentioning
confidence: 99%